TOURISM DESTINATION MANAGEMENT RECOVERY STRATEGY AND CULINARY BUSINESS ACTORS WITH CHSE DAN IMPLEMENTATION INFORMATION SYSTEM DESIGN SUPPORT (CASE STUDY OF DPSP BOROBUDUR) - Erna Wijayanti; Sugeng Santoso (Journal of Economics, Management, Entrepreneurship, and Business (JEMEB), 2022)
The research used in this research is Mixed Methods, descriptive research with qualitative and quantitative approaches. In the first stage, qualitative analysis was carried out with discussion and observation (survey) to the location directly. The key informants in this study were Magelang Regency Officials from the Tourism and Culture Office, and the Bappeda for the Management of DPSP Borobudur Culinary Business Actors at DPSP Borobudur. While the supporting informants are the Association of Culinary Actors, Association of Tourism Actors, Communities, Academics and the Ministry of Tourism and Creative Economy. The quantitative approach is carried out using the SEM method using 3 variables that will be the reference in the research, namely CHSE, recovery strategy, and information design. The tourism recovery strategy through the implementation of CHSE carried out in the management of the Borobudur DPSP destination includes obtaining CHSE certification, disciplining the application of health protocols, informing health services, checking body temperature, providing hand washing facilities, cleaning tourist transportation modes, checking tourist vaccination status. The recovery strategy for culinary business actors in the Borobudur DPSP area through the implementation of CHSE carried out such as obtaining CHSE certification, providing hand washing facilities, cleaning tables and chairs, making sales with the buffet concept. Information system design in an effort to restore the management of tourist destinations and culinary businesses of the Borobudur Temple DPSP in the form of an information system design so that it is known the CHSE indicators that are applied and their direct influence on policies implemented by the central government and local governments on the CHSE protocol implemented by intermediaries, destination managers tourism, and culinary entrepreneurs.